IKZF1 genetic variants rs4132601 and rs11978267 and acute lymphoblastic leukemia risk in Tunisian children: a casecontrol study - Sana, Mahjoub; Vera, Chayeb; Hedia, Zitouni; Rabeb M., Ghali; Haifa, Regaieg; Wassim Y., Almawi; Touhami, Mahjoub (BMC MEDICAL GENETICS, 2019)
Background Associations between IKZF1 gene variants and Acute Lymphoblastic Leukemia (ALL) was recently reported. We examined whether the common IKZF1 polymorphisms rs4132601 T/G and rs111978267 A/G are associated with ALL among a Tunisian pediatric cohort. Methods This case-control study involved 170 patients with ALL and 150 control subjects. SNP genotyping was performed by TaqMan® SNP Genotyping Assay.
Keywords: Acute lymphoblastic leukemia; Gene polymorphism; IKZF1, rs4132601; rs111978267